2019
DOI: 10.9734/jerr/2019/v6i416956
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Rainfall Intensity by Optimization Technique in Abeokuta, South-West, Nigeria

Abstract: The design of water resources engineering control structures is best achieved with adequate estimation of rainfall intensity over a particular catchment. To develop the rainfall intensity, duration and frequency (IDF) models, 25 year daily rainfall data were collected from Nigerian Meteorological Agency (NIMET) Abuja for Abeokuta. The annual maximum rainfall amounts with durations of 5, 10, 15, 20, 30, 45, 60, 90, 120, 180, 240, 300 and 420 minutes were extracted and subjected to frequency analysis using the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Regression and correlation analyses were used with most of the results presented as equations and in graphical form. Further studies by some scholars [17][18][19][20] examined the predictive ability of different types of IDF models for Abakaliki and selected cities in Southern Nigeria, respectively. They concluded that simple two parameter quotient IDF type model predicted higher intensity at duration equal or less than 30 minutes and also predicted lowest relative error.…”
Section: Rainfallmentioning
confidence: 99%
“…Regression and correlation analyses were used with most of the results presented as equations and in graphical form. Further studies by some scholars [17][18][19][20] examined the predictive ability of different types of IDF models for Abakaliki and selected cities in Southern Nigeria, respectively. They concluded that simple two parameter quotient IDF type model predicted higher intensity at duration equal or less than 30 minutes and also predicted lowest relative error.…”
Section: Rainfallmentioning
confidence: 99%
“…Model was stationary type. [69] Modeling rainfall intensity by optimization technique in Abeokuta, South-West, Nigeria.…”
Section: Authorsmentioning
confidence: 99%
“…Equation (2.4) is non-linear power law that was calibrated for c, m, a parameters using intensity, duration and return period values in Table 1 and Excel Optimization Solver [5]. Source: [15]…”
Section: Calibration Of Sherman (1931) Idf Modelmentioning
confidence: 99%
“…The result in Table 1 was subjected to Anderson-Darling test to ascertain the probability distribution that best fit the rainfall annual maximum amount. This is a nonparametric test of the equality of continuous, one dimensional probability distributions that can be used to compare a sample with a reference probability distribution [15]. Gumbel Extreme Value Type 1 (GEVT-1) and Log-Pearson Type -3 (LPT-3) best fit the rainfall intensities with significant values of 0.7570 and 0.7538 at 5% confidence level respectively.…”
Section: Goodness Of Fit Testmentioning
confidence: 99%
See 1 more Smart Citation